2013
DOI: 10.1308/003588413x13511609957939
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of endonasal dacryocystorhinostomy with and without stenting

Abstract: INTRODUCTION This study aimed to evaluate the short and long-term results of endoscopic dacryocystorhinostomy (DCR) with and without silicone stenting in chronic dacrocystorhinitis due to postsaccal blockage. METHODS The study involved a case series of consecutive 89 patients (128 eyes) who underwent endoscopic DCR. All patients were operated on by the senior author. The stent group comprised 63 eyes (44 patients), for which the DCR was performed between September 2002 and September 2005. The non-stent group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 17 publications
0
16
1
1
Order By: Relevance
“…Durvasula and Gatland12 conducted a postal survey of symptoms following endoscopic DCR in 70 patients, and reported successful outcomes in 83% at a mean follow-up of 28.6 months. Mohamad et al 13 compared the long-term outcomes of endoscopic DCR with relation to the presence or absence of stents in 89 patients. At a mean follow-up of 33 months, they found 89% to be successful in the non-stent group as compared to 57% in the stent group; the majority reported to result from rhinostomy closures.…”
Section: Discussionmentioning
confidence: 99%
“…Durvasula and Gatland12 conducted a postal survey of symptoms following endoscopic DCR in 70 patients, and reported successful outcomes in 83% at a mean follow-up of 28.6 months. Mohamad et al 13 compared the long-term outcomes of endoscopic DCR with relation to the presence or absence of stents in 89 patients. At a mean follow-up of 33 months, they found 89% to be successful in the non-stent group as compared to 57% in the stent group; the majority reported to result from rhinostomy closures.…”
Section: Discussionmentioning
confidence: 99%
“…]. Some authors believe that silicone tubes are too small in diameter to prevent future stenosis, and actually promote granulation and therefore increase the failure rate [22]. Table 3 lists the surgical outcomes of EN-DCR with and without SSI.…”
Section: Silicone Stentsmentioning
confidence: 99%
“…A retrospective study of 76 consecutive patients with epiphora, mucocele, or chronic dacryocystitis showed a higher success rate among patients who received silicone tubing compared with those who did not (94 versus 83%, respectively) [21], but the study was underpowered and did not reach statistical significance. A retrospective DCR study demonstrated functional success in 44 of 63 patients with stents and functional success (relief from epiphora) in 63 of 65 nonstented eyes 6 months after the operation [22]. The practice of using stents is controversial.…”
Section: Silicone Stentsmentioning
confidence: 99%
“…1,[14][15][16] The success rates of endoscopic DCR in acute dacryocystitis are reported up to 96.2% after primary and revision surgeries. Although long-term outcomes of primary endoscopic DCR for routine cases have been reported to be in the range of 81% to 97.7%, [17][18][19][20] very few studies analyzed the long-term outcomes in cases of acute dacryocystitis. 10,11,13 The purpose of present study is to report the long-term outcomes of powered endoscopic DCR in patients with acute dacryocystitis.…”
Section: Introductionmentioning
confidence: 99%